2017
DOI: 10.1055/s-0043-111013
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Mechanisms of Change in Body-Oriented Yoga in Major Depressive Disorders

Abstract: Abstr Ac tIntroduction Despite empirical evidence for the efficacy of body-oriented yoga as add-on treatment for major depressive disorder (MDD), the specific mechanisms by which yoga leads to therapeutic changes remain unclear. By means of a systematic review, we evaluate how the field is progressing in its empirical investigation of mechanisms of change in yoga for MDD.Methods To identify relevant studies, a systematic search was conducted.Results The search produced 441 articles, of which 5 were included, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
0
15
0
6
Order By: Relevance
“…In 1997, Singh and his colleagues randomized 32 older adults with depression to either a resistance exercise group or a control group, and they found depression was significantly improved after resistance exercise 21 . In recent years, Taijiquan and Yoga, which can be regarded as mind‐body exercise, have been accepted and loved by many people to relieve depression symptoms 22,23 . Here, we reviewed the antidepression effects of these three different types of exercise: aerobic exercise, resistance exercise, and mind‐body exercise (Table 1).…”
Section: Evidence Of Exercise Effect On Depressionmentioning
confidence: 99%
“…In 1997, Singh and his colleagues randomized 32 older adults with depression to either a resistance exercise group or a control group, and they found depression was significantly improved after resistance exercise 21 . In recent years, Taijiquan and Yoga, which can be regarded as mind‐body exercise, have been accepted and loved by many people to relieve depression symptoms 22,23 . Here, we reviewed the antidepression effects of these three different types of exercise: aerobic exercise, resistance exercise, and mind‐body exercise (Table 1).…”
Section: Evidence Of Exercise Effect On Depressionmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) and open studies have found yoga to be beneficial in treating unipolar depression. 19 22 On its own or as an adjunct to medication, yoga has been shown to alleviate symptoms of mild to moderate depression. 23 Preliminary evidence suggests that it may even benefit more severe depression and even alleviate suicidal ideation.…”
Section: Yoga For Depressionmentioning
confidence: 99%
“…Second, these subjects may experience more varied symptoms than healthy subjects because subjects of these groups reported numerous symptoms that healthy individuals did not report. For some, it may be di cult to take into consideration the characteristics of yoga, such as changing from a sympathetic-dominant state to being parasympathetic-dominant [23] [24]. Although this effect is bene cial for reducing stress [25], it is possible that it may cause or exacerbate coughing and runny noses in patients with bronchial asthma and allergic/vasomotor rhinitis, abdominal pain and diarrhea in patients with irritable bowel syndrome, and faintness or dizziness in patients with hypotension, especially orthostatic hypotension because these symptoms are induced or exacerbated by parasympathetic activation.…”
Section: Adverse Eventsmentioning
confidence: 99%